Molecular Study on Dengue Viruses of Patients in A Tertiary Care Hospital in Western Odisha - Ram, Sudipta kumar; Khatua, Sasmita; Hotta, Sasmita (Journal of Neonatal Surgery, 2025)
Background: As a viral disease caused by the Flavivirus transmitted by mosquitoes, Dengue is a common illness in tropical and subtropical countries with clinical manifestations from mild fever to complicated forms like Dengue Hemorrhagic Fever (DHF) and Dengue Shock Syndrome (DSS). Early diagnosis and specificity are important because there is no specific antiviral therapy or licensed vaccine available. Aim: To assess the usefulness of molecular diagnostics in dengue virus serotyping and correlate results with clinical and demographic profiles. Materials and Methods: 384 clinically suspected dengue patients according to WHO criteria were included. Serum was screened for antigen and antibodies by rapid tests and ELISA. Samples that were NS1 positive were also subjected to RT-PCR for detection of viral RNA and serotyping. Results: 70 ELISA positives were seen out of 384 samples. RT-PCR verification of DENV-1 and DENV-2 serotypes was seen, with the predominance of DENV-2. Infection was mostly seen in males, and among the male population, 15–30 years was most affected. The post-monsoon season saw the maximum cases, specifically in the month of October. The most frequent symptoms that were seen were fever, headache, myalgia, arthralgia, and manifestations of bleeding. Conclusion: ELISA is still a useful screening tool, and RT-PCR is useful for precise serotyping for effective surveillance. DENV-2 predominance with more severe clinical manifestations highlights the importance of ongoing vigilance and early detection, especially during peak risk periods.